Amoebic brain abscess associated with renal cell carcinoma. Issue 6 (15th October 2017) - Abdullah, Umme Hani; Baig, Mirza Zain; Azeemuddin, Muhammad; Wasay, Mohammad; Yakoob, Javed; Beg, Mohammad Asim
Abstract: Entamoeba histolytica is a protozoan parasite that is associated with diarrhea, but can extend to involve several organs. We report a case of amoebic brain abscess in a man who presented with fever, vomiting and headache with confusion and right hemiparesis. Brain magnetic resonance imaging showed a mass in the left frontal lobe, while abdominal computerized tomography showed a left renal malignancy. Brain biopsy showed Entamoeba histolytica infection. He was treated with intravenous metronidazole and nephrectomy that was followed by complete recovery. The present case report emphasizes that cerebral amoebiasis is associated with renal cell carcinoma.